Josephson coupling in high-Tc superconducting junctions using ultra-thin BaTiO3 barriers - Navarro, H. (2020)
Fil: Navarro, H. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; University of California; Estados Unidos